Equity risk premium: A cross country analysis on return behaviour - Kumar, Santhosh (Ushus Journal of Business Management, 2015)
The equity risk premium has been of paramount importance in the field of finance and is still a widely utilised central element for every risk return model in corporate finance, asset pricing and other fields of economic literature. This research captures the differences in the ex-post behaviour of equity risk premium between developed and emerging markets .Further, an investigation has been made into the impact of global integration on the ERP across G7 countries and 7 emerging countries. .The analysis has shown a decline in the ERP of developed nations and an upward trend in emerging markets over the chosen sub-sample period. We found out that there exists low correlation in ERP of emerging markets in comparison with developed markets